Ergonomics in Medical Equipment Development and System Design (International Journal of Innovative Research in Computer Science & Technology, 2017)
Utilizing ergonomics during medical equipment  development and system design increases patient safety and  efficiency in the working environment. The purpose of this report is to review the current literature on the use of  ergonomics during medical equipment development and  system design. To support the efficient use of existing  ergonomics, there are techniques and methods that form an  application for usage in the development process. The  literature review will illustrate heuristics, design methods and  design guidelines that ergonomists utilize during medical  equipment development and system design.
Keywords: Medical Equipment; Ergonomics, System; Design; Safety